A facile one-step synthesis and fabrication of hexagonal palladium-carbon nanocubes (H-Pd/C NCs) and their application as an efficient counter electrode for dye-sensitized solar cell (DSSC). Issue 11 (1st August 2017) - Vijayakumar, P.; Senthil Pandian, M.; Pandikumar, A.; Ramasamy, P.
Abstract: Hexagonal palladium-carbon nanocubes (H-Pd/C NCs) were prepared using a simple one-step chemical synthesis protocol and subsequently the prepared materials were used as the counter electrode (CE) in dye sensitized solar cell (DSSC) to replace the platinum (Pt) electrode. The H-Pd/C NCs were characterized by a variety of suitable analytical techniques including powder X-ray diffraction (PXRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and Brunauer–Emmett–Teller (BET) analysis to evaluate the crystalline, structural, morphological, compositional, chemical state and surface area. The BET nitrogen adsorption /desorption analysis shows that the as-prepared H-Pd/C NCs sample had a large surface area (568.8 m 2  g −1 ) with average pore size of ∼3 nm. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) analyses indicate that the H-Pd/C NCs have low charge-transfer resistance on the electrolyte/electrode interface and high electrocatalytic activity for the reduction of triiodide to iodide redox electrolyte and hence it is used as a CE in DSSC. The H-Pd/C NCs showed an overall power conversion efficiency (PCE) of 4.1% which performance is comparable with the conventional Pt CE (4.0%) under the identical condition.